Good Corporate Governance, Struktur Kepemilikan Dan Kinerja Perusahaan Properti dan Real Estate - Gabriella Pingkan Larasati Prasetya; Awan Santosa (CAPITAL: Jurnal Ekonomi dan Manajemen, 2020)
This study aims to examine the GCG and ownership structure of company performance in the property and real estate sub-sector manufacturing companies listed on the Stock Exchange in the 2016-2018 period. The type of research used is quantitative research. The sample of this research used purposive sampling technique so that the samples obtained were 14 companies. analysis used classic assumptions, multiple regression, multiple correlations, coefficient terminated, t test, F test. the results showed that the audit committee affected the company's performance both ROA and EPS, the independent board of commissioners did not affect the company's performance both ROA and EPS, ownership inatitusioanal does not affect the performance of companies with ROA proxies, but with EPS Proxies institutional ownership affects company performance and managerial ownership does not affect company performance both ROA and EPS.keywords: Good Corporate Governance (GCG), ownership structure, company performance, institutional ownership, managerial ownership.